Peningkatan Keterampilan Kelompok Julu Atia melalui Pelatihan Pembuatan Nugget Rumput Laut - Kasmiati, Kasmiati; Andriani, Irma; Massi, Muh. Nasrum; Rahmi, Rahmi; Anas, Lukman; Zakiyabarsi, Furqan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
Seaweed is a leading commodity in the fisheries sector that has not been optimally utilized, particularly by community groups, to increase its added value. The problem faced by these groups is a lack of knowledge and skills in processing and selling seaweed-based products. This activity aims to improve the knowledge and skills of "Julu Atia" partners in the production and marketing of seaweed nuggets. The method used was to directly involve 20 members in training and mentoring activities. The training included counseling and practical training on nugget production and marketing, while the mentoring aimed to evaluate the group's ability to independently produce and market the product. Initial knowledge and skills of partners were determined through pre- and post-tests. The results showed that partner knowledge was relatively low, with an average of 34.5%, increasing by 55% to 89.5% after participating in the community service activity. Through nugget production, the added value increased by IDR 222,000 per kg of seaweed. Thus, this activity effectively increased the empowerment level of "Julu Atia" and can be replicated in other groups to improve the welfare of coastal communities.